Aroma profile of Montepulciano d’Abruzzo wine fermented by single and co-culture starters of autochthonous Saccharomyces and non-Saccharomyces yeasts - Rosanna eTofalo; Francesca ePatrignani; Rosalba eLanciotti; Giorgia ePerpetuini; Maria eSchirone; Paola eDi Gianvito; Daniel ePizzoni; Giuseppe eArfelli; Giovanna eSuzzi (Frontiers in Microbiology, 2016)
Montepulciano d’Abruzzo is a native grape variety of Vitis vinifera L., grown in central Italy and used for production of high quality red wines. Limited studies have been carried out to improve its enological characteristics through the use of indigenous strains of Saccharomyces cerevisiae. The main objective of the present work was to test two indigenous strains of S. cerevisiae (SRS1, RT73), a strain of Starm. bacillaris (STS12), one of H. uvarum (STS45) and a co-culture of S. cerevisiae (SRS1) and Starm. bacillaris (STS12), in an experimental cellar to evaluate their role in the sensory characteristic of Montepulciano d’Abruzzo wine. A S. cerevisiae commercial strain was used. Fermentations were conducted under routine Montepulciano d’Abruzzo wine production, in which the main variables were the yeast strains used for fermentation. Basic winemaking parameters, some key chemical analysis and aroma compounds were considered. Saccharomyces cerevisiae strain dynamics during fermentation were determined by molecular methods. The musts inoculated with the co-culture were characterized by a faster fermentation start and a higher content of glycerol after three days of fermentation, as well as the musts added with strains Starm. bacillaris (STS12) and H. uvarum (STS45). At the end of fermentation the parameters studied were quite similar in all the wines. Total biogenic amines (BA) content of all the wines was low. Ethanolamine was the predominant BA, with a concentration ranging from 21 to 24 mg/l. Wines were characterized by esters and alcohols. In particular, 2-phenylethanol, 3-methylbut-1-yl methanoate and ethyl ethanoate were the major aroma volatile compounds in all wines. Statistical analysis highlighted the different role played by aroma compounds in the differentiation of wines, even if it was impossible to select a single class as the most important for a specific yeast. The present study represents a further step towards the use of tailored autochthonous strains to impart the specific characteristics of a given wine which are an expression of a specific terroir